ANALISIS REPURCHASE BEHAVIOR PADA CHANDRA SUPERSTORE TANJUNG KARANG - Benediktus Tedi Yulianto; Ardiyansyah Amr (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2019)
This Research aims to find how much influence between the perceptions of prices byconsumers on consumer repurchase behavior. In this study analyze the problems and prove thehypothesis by using the method of observation with quantitative approach survey, the data used isprimary data is data that researchers obtain directly in the field. The result of significant level shows50,53% and based on calculation of coefficient of determination (R2) is relatively small that is equal to0,207. Means that price perceptions affect 20.7% of repurchase behavior.Suggestion of improvement, regarding the clean and neat shopping place, to be repaired sothat consumers feel satisfied with the perception of quality received in accordance with the cost incurredin shopping at Chandra Superstore Tanjung Karang Bandar Lampung.Suggested improvements,enhance the reputation of shopping facilities that make consumers more comfortable shopping that willmake consumers more often re-shop at Chandra Superstore Tanjung Karang Bandar Lampung and rechoose a strategic location in the development.